Ablation of Protein Kinase CK2β in Skeletal Muscle Fibers Interferes with Their Oxidative Capacity - Eiber, Nane; Simeone, Luca; Hashemolhosseini, Said (Pharmaceuticals, 2017)
The tetrameric protein kinase CK2 was identified playing a role at neuromuscular junctions by studying CK2β-deficient muscle fibers in mice, and in cultured immortalized C2C12 muscle cells after individual knockdown of CK2α and CK2β subunits. In muscle cells, CK2 activity appeared to be at least required for regular aggregation of nicotinic acetylcholine receptors, which serves as a hallmark for the presence of a postsynaptic apparatus. Here, we set out to determine whether any other feature accompanies CK2β-deficient muscle fibers. Hind limb muscles gastrocnemius, plantaris, and soleus of adult wildtype and CK2β-deficient mice were dissected, cross-sectioned, and stained histochemically by Gomori trichrome and for nicotinamide adenine dinucleotide (NADH) dehydrogenase and succinate dehydrogenase (SDH) enzymatic activities. A reduction of oxidative enzymatic activity was determined for CK2β-deficient muscle fibers in comparison with wildtype controls. Importantly, the CK2β-deficient fibers, muscle fibers that typically exhibit high NADH dehydrogenase and SDH activities, like slow-type fibers, showed a marked reduction in these activities. Altogether, our data indicate additional impairments in the absence of CK2β in skeletal muscle fibers, pointing to an eventual mitochondrial myopathy.
EVALuna2:33489

Casein kinase 2-dependent serine phosphorylation of MuSK regulates acetylcholine receptor aggregation at the neuromuscular junction. - Cheusova, Tatiana; Khan, Muhammad A.; Schubert, Steffen; Gavin, Anne-Claude; Buchou, Thierry; Jacob, Germaine; Sticht, Heinrich; Allende, Jorge; Boldyreff, Brigitte; Brenner, Hans Rudolf; Hashemolhosseini, Said (Genes & Development, 2006)
The release of Agrin by motoneurons activates the muscle-specific receptor tyrosine kinase (MuSK) as the main organizer of subsynaptic specializations at the neuromuscular junction. MuSK downstream signaling is largely undefined. Here we show that protein kinase CK2 interacts and colocalizes with MuSK at post-synaptic specializations. We observed CK2-mediated phosphorylation of serine residues within the kinase insert (KI) of MuSK. Inhibition or knockdown of CK2, or exchange of phosphorylatable serines by alanines within the KI of MuSK, impaired acetylcholine receptor (AChR) clustering, whereas their substitution by residues that imitate constitutive phosphorylation led to aggregation of AChRs even in the presence of CK2 inhibitors. Impairment of AChR cluster formation after replacement of MuSK KI with KIs of other receptor tyrosine kinases correlates with potential CK2-dependent serine phosphorylation within KIs. MuSK activity was unchanged but AChR stability decreased in the presence of CK2 inhibitors. Muscle-specific CK2β knockout mice develop a myasthenic phenotype due to impaired muscle endplate structure and function. This is the first description of a regulatory cross-talk between MuSK and CK2 and of a role for the KI of the receptor tyrosine kinase MuSK for the development of subsynaptic specializations. © 2006 by Cold Spring Harbor Laboratory Press.
UnivIS-Import:2015-03-09:Pub.2006.med.IB.LPCIPDBI.casein
Keywords: Casein kinase; CK2; MuSk; Neuromuscular junction; Skeletal muscle; Synapse

Collagen VI is required for the structural and functional integrity of the neuromuscular junction - Cescon, Matilde; Gregorio, Ilaria; Eiber, Nane; Borgia, Doriana; Fusto, Aurora; Sabatelli, Patrizia; Scorzeto, Michele; Megighian, Aram; Pegoraro, Elena; Hashemolhosseini, Said; Bonaldo, Paolo (Acta Neuropathologica, 2018)
The synaptic cleft of the neuromuscular junction (NMJ) consists of a highly specialized extracellular matrix (ECM) involved in synapse maturation, in the juxtaposition of pre- to post-synaptic areas, and in ensuring proper synaptic transmission. Key components of synaptic ECM, such as collagen IV, perlecan and biglycan, are binding partners of one of the most abundant ECM protein of skeletal muscle, collagen VI (ColVI), previously never linked to NMJ. Here, we demonstrate that ColVI is itself a component of this specialized ECM and that it is required for the structural and functional integrity of NMJs. In vivo, ColVI deficiency causes fragmentation of acetylcholine receptor (AChR) clusters, with abnormal expression of NMJ-enriched proteins and re-expression of fetal AChRγ subunit, both in Col6a1 null mice and in patients affected by Ullrich congenital muscular dystrophy (UCMD), the most severe form of ColVI-related myopathies. Ex vivo muscle preparations from ColVI null mice revealed altered neuromuscular transmission, with electrophysiological defects and decreased safety factor (i.e., the excess current generated in response to a nerve impulse over that required to reach the action potential threshold). Moreover, in vitro studies in differentiated C2C12 myotubes showed the ability of ColVI to induce AChR clustering and synaptic gene expression. These findings reveal a novel role for ColVI at the NMJ and point to the involvement of NMJ defects in the etiopathology of ColVI-related myopathies.
EVALuna2:35740

Conservation and variation of structure and function in a newly identified GCM homolog from chicken - Wegner, Michael; Hashemolhosseini, Said; et al. (Journal of Molecular Biology, 2004)
Glial cell missing (GCM) proteins constitute a small family of transcription factors with two members each described in Drosophila and several mammalian species. Here, we report the identification of a GCM homolog from chicken. Although the exon-intron structure is well conserved between chicken GCM and other family members, sequence similarity is largely restricted to the DNA-binding GCM-domain (residues 24-176). In accord with the high degree of sequence conservation within the GCM-domain, the chicken GCM protein has a DNA-binding specificity similar to that of other GCM proteins. Like other GCM proteins, it is located to the nucleus and can act as a transcriptional activator despite the strong divergence in sequences outside the GCM-domain. The chicken GCM protein contains two transactivation domains with cell-specific function, one immediately following the DNA-binding domain, the other at its extreme carboxy terminus. Intriguingly, chicken GCM is expressed only transiently during embryogenesis and is restricted exclusively to extraembryonic tissues where it was detected in close vicinity to embryonic blood vessels. Taking the extraembryonic expression of chicken GCM and mammalian GCMa into account, it is tempting to speculate that a conserved extraembryonic function exists for GCM proteins in birds and mammals. © 2003 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2004.med.IB.LPCIPDBI.conser
Keywords: Gcm-1; GCMa; Glial cells missing; Placenta

EPISODIC PSYCHOSIS, ATAXIA, MOTOR NEUROPATHY CAUSED BY A NOVEL MUTATION IN ADPRHL2 - Durmus, Hacer; Sticht, Heinrich; Ceylaner, Serdar; Hashemolhosseini, Said; Parmn, Yesim (NEUROLOGY, 2020)
CRIS-Team WoS Importer:2020-08-21

Episodic psychosis, ataxia, motor neuropathy with pyramidal signs (PAMP sydrome) caused by a novel mutation in ADPRHL2 (AHR3) - Durmus, Hacer; Mertoğlu, Elif; Sticht, Heinrich; Ceylaner, Serdar; Kulaksızoğlu, Işın Baral; Hashemolhosseini, Said; Uçar, Evren Önay; Parman, Yesim (Neurological Sciences, 2021)
Background: The protein “ADP-Ribosylarginine Hydrolase-Like Protein 2” is encoded by ADPRHL2 and reverses ADP-ribosylation. Recently, mutations in ADPRHL2 were found to be associated with a very rare childhood onset severe neurodegeneration syndrome with episodic, stress-induced seizures, ataxia, and axonal neuropathy. In this study, we evaluate a novel mutation in ADPRHL2 leading to an unknown adult onset syndrome “episodic psychosis, ataxia, motor neuropathy with pyramidal signs (PAMP syndrome).” Design/methods: Four patients with episodic psychosis, ataxia, and motor neuropathy with pyramidal signs were included in this study. Results: An index patient presented ataxia, postural tremor in the hands, and hallucinations at age 20 years, which had started after a viral infection. She improved within 3 months without any treatment. Her neurological exam revealed mild distal weakness, brisk DTRs, bilateral Babinski sign, impaired vibration sensation, position, and ataxia. Pes cavus and hammer toes were also noted. EMG revealed neurogenic changes in distal muscles and normal sensory nerve conduction studies. Cranial MRI was normal. She had three more severe episodes in recent years, and her neurologic findings got progressively worse. Two of her older sisters had much milder phenotypes. The phenotype of the fourth patient from an unrelated family was identical with the index patient. All affected patients had homozygous novel NM_017825.3:c.838G>A (p.Ala280Thr) mutations in a highly conserved region of ADPRHL2. Western blot analyses demonstrated that ADPRHL2 was not expressed in these patients. Conclusions: Here, we describe a novel mutation in ADPRHL2, which further expands the phenotypic and genetic spectrum of the patients harboring these mutations.
CRIS-Team Scopus Importer:2021-02-12
Keywords: ADPRHL2; AHR3; Ataxıa; Epısodıc psychosıs; Motor neuropathy

GCMB mutation in familial isolated hypo-parathyroidism with residual secretion of parathyroid hormone. - Wegner, Michael; Hashemolhosseini, Said; et al. (Journal of Clinical Endocrinology and Metabolism, 2005)
UnivIS-Import:2015-03-09:Pub.2005.med.IB.LPCIPDBI.gcmbmu

Identification of developmentally regulated expression of MuSK in astrocytes of the rodent retina. - Cheusova, Tatiana; Khan, Muhammad Amir; Enz, Ralf; Hashemolhosseini, Said (Journal of Neurochemistry, 2006)
One of the master regulators of postsynaptic neuromuscular synaptogenesis is the muscle-specific receptor tyrosine kinase (MuSK). In mammals prominent MuSK expression is believed to be restricted to skeletal muscle. Upon activation by nerve-derived agrin MuSK-dependent signalling participates in both the induction of genes encoding postsynaptic components and aggregation of nicotinic acetylcholine receptors (AChR) in the subsynaptic muscle membrane. Strikingly, expression of certain isoforms of nerve-derived agrin can also be detected in the CNS. In this study, we examined the expression of MuSK in the brain and eye of rodents. In the retina MuSK was expressed in astrocytes between postnatal days 7 and 14, i.e. at the time when the eyes open. We found that agrin was localized adjacent to MuSK-expressing astrocytes which in turn were detected close to the inner limiting membrane of the rodent retina. In summary, the presence of MuSK on retinal astrocytes suggests a novel role of MuSK signalling pathways in the CNS. © 2006 The Authors.
UnivIS-Import:2015-04-14:Pub.2006.med.IB.LPCIPDBI.identi
Keywords: Agrin; Astrocytes; Eye; Muscle-specific receptor tyrosine kinase; Neuromuscular junction; Retina

Impacts of a new trancription factor family: Mammalian GCM proteins in health and disease. - Wegner, Michael; Hashemolhosseini, Said (The Journal of Cell Biology, 2004)
UnivIS-Import:2015-03-09:Pub.2004.med.IB.LPCIPDBI.impact

In Adult Skeletal Muscles, the Co-Receptors of Canonical Wnt Signaling, Lrp5 and Lrp6, Determine the Distribution and Size of Fiber Types, and Structure and Function of Neuromuscular Junctions - Geßler, Lea; Kurtek, Christopher; Merholz, Mira; Jian, Yongzhi; Hashemolhosseini, Said (Cells, 2022)
Canonical Wnt signaling is involved in skeletal muscle cell biology. The exact way in which this pathway exerts its contribution to myogenesis or neuromuscular junctions (NMJ) is a matter of debate. Next to the common co-receptors of canonical Wnt signaling, Lrp5 and Lrp6, the receptor tyrosine kinase MuSK was reported to bind at NMJs WNT glycoproteins by its extracellular cysteine-rich domain. Previously, we reported canonical Wnt signaling being active in fast muscle fiber types. Here, we used conditional Lrp5 or Lrp6 knockout mice to investigate the role of these receptors in muscle cells. Conditional double knockout mice died around E13 likely due to ectopic expression of the Cre recombinase. Phenotypes of single conditional knockout mice point to a very divergent role for the two receptors. First, muscle fiber type distribution and size were changed. Second, canonical Wnt signaling reporter mice suggested less signaling activity in the absence of Lrps. Third, expression of several myogenic marker genes was changed. Fourth, NMJs were of fragmented phenotype. Fifth, recordings revealed impaired neuromuscular transmission. In sum, our data show fundamental differences in absence of each of the Lrp co-receptors and suggest a differentiated view of canonical Wnt signaling pathway involvement in adult skeletal muscle cells.
CRIS-Team WoS Importer:2023-01-20

In mammalian skeletal muscle, phosphorylation of TOMM22 by protein kinase CSNK2/CK2 controls mitophagy - Kravic, Bojana; Harbauer, Angelika B.; Romanello, Vanina; Simeone, Luca; Vögtle, F. Nora; Kaiser, Tobias; Straubinger, Marion; Huraskin, Danyil; Böttcher, Martin; Cerqua, Cristina; Martin, Eva Denise; Poveda-Huertes, Daniel; et al. (Autophagy, 2017)
In yeast, Tom22 the central component of the TOMM (translocase of outer mitochondrial membrane) receptor complex is responsible for the recognition and translocation of synthesized mitochondrial precursor proteins, and its protein kinase CK2-dependent phosphorylation is mandatory for TOMM complex biogenesis and proper mitochondrial protein import. In mammals, the biological function of protein kinase CSNK2/CK2 remains vastly elusive and it is unknown whether CSNK2-dependent phosphorylation of TOMM protein subunits has a similar role as that in yeast. To address this issue, we used a skeletal muscle-specific Csnk2b/Ck2?-conditional knockout (cKO) mouse model. Phenotypically, these skeletal muscle Csnk2b cKO mice showed reduced muscle strength and abnormal metabolic activity of mainly oxidative muscle fibers, which point towards mitochondrial dysfunction. Enzymatically, active muscle lysates from skeletal muscle Csnk2b cKO mice phosphorylate murine TOMM22, the mammalian ortholog of yeast Tom22, to a lower extent than lysates prepared from controls. Mechanistically, CSNK2-mediated phosphorylation of TOMM22 changes its binding affinity for mitochondrial precursor proteins. However, in contrast to yeast, mitochondrial protein import seems not to be affected in vitro using mitochondria isolated from muscles of skeletal muscle Csnk2b cKO mice. PINK1, a mitochondrial health sensor that undergoes constitutive import under physiological conditions, accumulates within skeletal muscle Csnk2b cKO fibers and labels abnormal mitochondria for removal by mitophagy as demonstrated by the appearance of mitochondria-containing autophagosomes through electron microscopy. Mitophagy can be normalized by either introduction of a phosphomimetic TOMM22 mutant in cultured myotubes, or by in vivo electroporation of phosphomimetic Tomm22 into muscles of mice. Importantly, transfection of the phosphomimetic Tomm22 mutant in muscle cells with ablated Csnk2b restored their oxygen consumption rate comparable to wild-type levels. In sum, our data show that mammalian CSNK2-dependent phosphorylation of TOMM22 is a critical switch for mitophagy and reveal CSNK2-dependent physiological implications on metabolism, muscle integrity and behavior.
EVALuna2:25775

In Skeletal Muscle Fibers, Protein Kinase Subunit CSNK2A1/CK2 alpha Is Required for Proper Muscle Homeostasis and Structure and Function of Neuromuscular Junctions - Merholz, Mira; Jian, Yongzhi; Wimberg, Johannes; Geßler, Lea; Hashemolhosseini, Said (Cells, 2022)
CSNK2 tetrameric holoenzyme is composed of two subunits with catalytic activity (CSNK2A1 and/or CSNK2A2) and two regulatory subunits (CSNK2B) and is involved in skeletal muscle homeostasis. Up-to-date, constitutive Csnk2a2 knockout mice demonstrated mild regenerative impairments in skeletal muscles, while conditional Csnk2b mice were linked to muscle weakness, impaired neuromuscular transmission, and metabolic and autophagic compromises. Here, for the first time, skeletal muscle-specific conditional Csnk2a1 mice were generated and characterized. The ablation of Csnk2a1 expression was ensured using a human skeletal actin-driven Cre reporter. In comparison with control mice, first, conditional knockout of CSNK2A1 resulted in age-dependent reduced grip strength. Muscle weakness was accompanied by impaired neuromuscular transmission. Second, the protein amount of other CSNK2 subunits was aberrantly changed. Third, the number of central nuclei in muscle fibers indicative of regeneration increased. Fourth, oxidative metabolism was impaired, reflected by an increase in cytochrome oxidase and accumulation of mitochondrial enzyme activity underneath the sarcolemma. Fifth, autophagic processes were stimulated. Sixth, NMJs were fragmented and accompanied by increased synaptic gene expression levels. Altogether, knockout of Csnk2a1 or Csnk2b results in diverse impairments of skeletal muscle biology.
CRIS-Team WoS Importer:2023-01-06

Lack of Desmin in Mice Causes Structural and Functional Disorders of Neuromuscular Junctions - Eiber, Nane; Fröb, Franziska; Schowalter, Mirjam; Thiel, Christian; Clemen, Christoph S.; Schröder, Rolf; Hashemolhosseini, Said (Frontiers in Molecular Neuroscience, 2020)
Desmin, the major intermediate filament (IF) protein in muscle cells, interlinks neighboring myofibrils and connects the whole myofibrillar apparatus to myonuclei, mitochondria, and the sarcolemma. However, desmin is also known to be enriched at postsynaptic membranes of neuromuscular junctions (NMJs). The pivotal role of the desmin IF cytoskeletal network is underscored by the fact that over 120 mutations of the human DES gene cause hereditary and sporadic myopathies and cardiomyopathies. A subgroup of human desminopathies comprises autosomal recessive cases resulting in the complete abolition of desmin protein. In these patients, who display a more severe phenotype than the autosomal dominant cases, it has been reported that some individuals also suffer from a myasthenic syndrome in addition to the classical occurrence of myopathy and cardiomyopathy. Since further studies on the NMJ pathology are hampered by the lack of available human striated muscle biopsy specimens, we exploited homozygous desmin knock-out mice which closely mirror the striated muscle pathology of human patients lacking desmin protein. Here, we report on the impact of the lack of desmin on the structure and function of NMJs and the transcription of genes coding for postsynaptic proteins. Desmin knock-out mice display a fragmentation of NMJs in soleus, but not in the extensor digitorum longus muscle. Moreover, soleus muscle fibers show larger NMJs. Further, transcription levels of acetylcholine receptor (AChR) genes are increased in muscles from desmin knock-out mice, especially of the AChR gamma subunit, which is known as a marker of muscle fiber regeneration. Electrophysiological recordings depicted a pathological decrement of nerve-dependent endplate potentials and an increased rise time of the nerve-independent miniature endplate potentials. The latter appears related to the fragmentation of NMJs in desmin knockout mice. Our study highlights the essential role of desmin for the structural and functional integrity of mammalian NMJs.
CRIS-Team WoS Importer:2020-11-27

LAP proteins are localized at the post-synaptic membrane of neuromuscular junctions and appear to modulate synaptic morphology and transmission - Kravic, Bojana; Huraskin, Danyil; Frick, Alexander; Jung, Jasmin; Redai, Veronika; Palmisano, Ralf; Marchetto, Sylvie; Borg, Jean-Paul; Mei, Lin; Hashemolhosseini, Said (Journal of Neurochemistry, 2016)
Erbin, Lano, Scribble, and Densin-180 belong to LAP (leucine-rich repeats and PDZ domain) adaptor proteins involved in cell signaling pathways. Previously, we identified Erbin, Lano, and Scribble, but not Densin-180, in muscle cells, where they are involved in regulating the aggregation of nicotinic acetylcholine receptors in vitro. Here, we analyzed their cellular localization at the neuromuscular junction (NMJ) in skeletal muscles of mice. Erbin, Lano, and Scribble were significantly accumulated at NMJs and localized in different synaptic cells. Moreover, we used mouse mutants to analyze the role of Erbin at the NMJ. We used two Erbin mutant mouse strains that either completely lack Erbin protein (Erbin(null/null) ) or express a truncated Erbin mutant where the carboxy-terminal PDZ domain is replaced by ?-galactosidase (Erbin(?C/?C) ) thereby abolishing its interaction with ErbB receptor tyrosine kinases. Neither the lack of the PDZ domain of Erbin, nor its complete absence interfered with the general localization of LAP proteins at NMJs, but Lano and Scribble transcript levels were up-regulated in homozygous Erbin-null muscles. Furthermore, grip strength was reduced and neural transmission impaired in homozygous aged Erbin-null but not Erbin-?C mice. Erbin-null skeletal muscles did not reveal any conspicuous impairment of the muscle fiber. Localization of other NMJ marker proteins was not affected either. Quantitative 3D morphometry showed that NMJs of Erbin-null muscles were significantly smaller and fragmented in the soleus. We speculate that Erbin, Lano, and Scribble act at the post-synaptic membrane of NMJs in a concerted fashion to regulate nicotinic acetylcholine receptors cluster morphology and neural transmission. Cover Image for this issue: doi: 10.1111/jnc.13340.
EVALuna2:4995

Loss of Protein Kinase Csnk2b/CK2 beta at Neuromuscular Junctions Affects Morphology and Dynamics of Aggregated Nicotinic Acetylcholine Receptors, Neuromuscular Transmission, and Synaptic Gene Expression - Eiber, Nane; Rehman, Michael; Kravic, Bojana; Rudolf, Ruediger; Sandri, Marco; Hashemolhosseini, Said (Cells, 2019)
The protein kinase Csnk2/CK2 is important for cell proliferation, differentiation, and survival. Previously, we showed that CK2 binds distinctive proteins at neuromuscular junctions (NMJs) of mice and phosphorylates some of them. CK2 likely stabilizes clustered nicotinic acetylcholine receptors (AChRs). In the absence of the beta-subunit of CK2 in skeletal muscle fibers, mice develop an age-dependent decrease of grip strength accompanied by NMJ fragmentation and impairments of neuromuscular transmission. However, the precise role of CK2 beta regarding the clustering of AChRs and downstream signaling at NMJs is unknown. Here, we compared conditional CK2 beta-deficient mice with controls and found in the mutants (1) a lower decrement of endplate potentials after repetitive stimulation and decrements of nerve-evoked compound muscle action potentials decayed more rapidly after synaptic transmission was partially blocked, (2) that their muscle weakness was partially rescued by administration of an acetylcholine esterase inhibitor, (3) fragmented NMJs and impaired AChR clustering was detected in muscles and cultured muscle cells, (4) enlarged myonuclei, (5) impaired synaptic gene expression, and (6) a high turnover rate of their AChR clusters in vivo. Altogether, our data demonstrate a role for CK2 at the NMJ by maintaining a high density of AChRs and ensuring physiological synaptic gene expression.
CRIS-Team WoS Importer:2019-09-24

Methocarbamol blocks muscular Nav1.4 channels and decreases isometric force of mouse muscles - Zhang, Yaxin; Otto, Philipp; Qin, Lu; Eiber, Nane; Hashemolhosseini, Said; Kröger, Stephan; Brinkmeier, Heinrich (Muscle & Nerve, 2020)
Background: The muscle relaxant methocarbamol is widely used for the treatment of muscle spasms and pain syndromes. To elucidate molecular mechanisms of its action, we studied its influence on neuromuscular transmission, on isometric muscle force, and on voltage-gated Na+ channels. Methods: Neuromuscular transmission was investigated in murine diaphragm-phrenic nerve preparations and muscle force studied on mouse soleus muscles. Nav1.4 channels and Nav1.7 channels were functionally expressed in eukaryotic cell lines. Results: Methocarbamol, at 2 mM, decreased the decay of endplate currents, slowed the decay of endplate potentials and reduced tetanic force of soleus muscles. The drug reversibly inhibited current flow through muscular Nav1.4 channels, while neuronal Nav1.7 channels were unaffected. Conclusions: The study provides evidence for peripheral actions of methocarbamol on skeletal muscle. Muscular Na+ channels are a molecular target of methocarbamol. Since Nav1.7 currents were unaffected, methocarbamol is unlikely to exert its analgesic effect by directly blocking Nav1.7 channels.
CRIS-Team Scopus Importer:2020-11-06
Keywords: methocarbamol; muscle force; muscle relaxant; neuromuscular transmission; voltage-gated Na

MicroRNAs promote skeletal muscle differentiation of mesodermal iPSC-derived progenitors - Giacomazzi, Giorgia; Holvoet, Bryan; Trenson, Sander; Caluwe, Ellen; Kravic, Bojana; Grosemans, Hanne; Cortes-Calabuig, Alvaro; Deroose, Christophe M.; Huylebroeck, Danny; Hashemolhosseini, Said; Janssens, Stefan; Mcnally, Elizabeth; et al. (Nature Communications, 2017)
Muscular dystrophies (MDs) are often characterized by impairment of both skeletal and cardiac muscle. Regenerative strategies for both compartments therefore constitute a therapeutic avenue. Mesodermal iPSC-derived progenitors (MiPs) can regenerate both striated muscle types simultaneously in mice. Importantly, MiP myogenic propensity is influenced by somatic lineage retention. However, it is still unknown whether human MiPs have in vivo potential. Furthermore, methods to enhance the intrinsic myogenic properties of MiPs are likely needed, given the scope and need to correct large amounts of muscle in the MDs. Here, we document that human MiPs can successfully engraft into the skeletal muscle and hearts of dystrophic mice. Utilizing non-invasive live imaging and selectively induced apoptosis, we report evidence of striated muscle regeneration in vivo in mice by human MiPs. Finally, combining RNA-seq and miRNA-seq data, we define miRNA cocktails that promote the myogenic potential of human MiPs.
EVALuna2:33478

Neuromuscular endplate pathology in recessive desminopathies: Lessons from man and mice - Durmus, Hacer; Ayhan, Ozgecan; Cirak, Sebahattin; Deymeer, Feza; Parman, Yesim; Franke, Andre; Eiber, Nane; Chevessier, Frederic; Schlötzer-Schrehardt, Ursula; Clemen, Christoph S.; Hashemolhosseini, Said; Schröder, Rolf; et al. (Neurology, 2016)
To assess the clinical, genetic, and myopathologic findings in 2 cousins with lack of desmin, the response to salbutamol in one patient, and the neuromuscular endplate pathology in a knock-in mouse model for recessive desminopathy.We performed clinical investigations in the patients, genetic studies for linkage mapping, exome sequencing, and qPCR for transcript quantification, assessment of efficacy of (3-month oral) salbutamol administration by muscle strength assessment, 6-minute walking test (6MWT), and forced vital capacity, analysis of neuromuscular endplate pathology in a homozygous R349P desmin knock-in mouse by immunofluorescence staining of the hind limb muscles, and quantitative 3D morphometry and expression studies of acetylcholine receptor genes by quantitative PCR.Both patients had infantile-onset weakness and fatigability, facial weakness with bilateral ptosis and ophthalmoparesis, generalized muscle weakness, and a decremental response over 10% on repetitive nerve stimulation. Salbutamol improved 6MWT and subjective motor function in the treated patient. Genetic analysis revealed previously unreported novel homozygous truncating desmin mutation c.345dupC leading to protein truncation and consequent fast degradation of the mutant mRNA. In the recessive desminopathy mouse with low expression of the mutant desmin protein, we demonstrated fragmented motor endplates with increased surface areas, volumes, and fluorescence intensities in conjunction with increased ? and ? acetylcholine receptor subunit expression in oxidative soleus muscle.The patients were desmin-null and had myopathy, cardiomyopathy, and a congenital myasthenic syndrome. The data from man and mouse demonstrate that the complete lack as well as the markedly decreased expression of mutant R349P desmin impair the structural and functional integrity of neuromuscular endplates.
EVALuna2:4994

Protein kinase CK2 interacts at the neuromuscular synapse with Rapsyn, Rac1, 14-3-3?, and Dok-7 proteins and phosphorylates the latter two - Herrmann, Dustin; Straubinger, Marion; Hashemolhosseini, Said (Journal of Biological Chemistry, 2015)
Previously, we demonstrated that the protein kinase CK2 associates with and phosphorylates the receptor tyrosine kinase MuSK (muscle specific receptor tyrosine kinase) at the neuromuscular junction (NMJ), thereby preventing fragmentation of the NMJs (Cheusova, T., Khan, M. A., Schubert, S. W., Gavin, A. C., Buchou, T., Jacob, G., Sticht, H., Allende, J., Boldyreff, B., Brenner, H. R., and Hashemolhosseini, S. (2006) Genes Dev. 20, 1800-1816). Here, we asked whether CK2 interacts with other proteins involved in processes at the NMJ, which would be consistent with the previous observation that CK2 appears enriched at the NMJ. We identified the following proteins to interact with protein kinase CK2: (a) the ? and ? subunits of the nicotinic acetylcholine receptors with weak interaction, (b) dishevelled (Dsh), and (c) another four proteins, Rapsyn, Rac1, 14-3-3?, and Dok-7, with strong interaction. CK2 phosphorylated 14-3-3? at serine residue 235 and Dok-7 at several serine residues but does not phosphorylate Rapsyn or Rac1. Furthermore, phosphomimetic Dok-7 mutants aggregated nicotinic acetylcholine receptors in C2C12 myotubes with significantly higher frequency than wild type Dok-7. Additionally, we mapped the interacting epitopes of all four binding partners to CK2 and thereby gained insights into the potential role of the CK2/Rapsyn interaction.
EVALuna2:4975

Rare slow channel congenital myasthenic syndromes without repetitive compound muscle action potential and dramatic response to low dose fluoxetine - Durmus, Hacer; Sticht, Heinrich; Ceylaner, Serdar; Hashemolhosseini, Said; Deymeer, Feza (Acta Neurologica Belgica, 2020)
Congenital myasthenic syndromes are rare hereditary disorders caused by mutations associated with proteins of the neuromuscular junction. Abnormal ‘‘gain of function’’ mutations result in prolonged nicotinic acetylcholine receptor channel open state causing a rare subtype of CMS, slow-channel CMS (SCCMS). Mutations in the delta subunit encoding the gene, CHRND, resulting in SCCMS are extremely rare. An important clue to the diagnosis of SCCMS is repetitive CMAP’s. Fluoxetine, usually at high doses, is used to treat SCCMS. The mutation, recently described in one patient, was identified by whole exome sequencing and validated, and its segregation with the disease was ascertained by Sanger sequencing. Here, we describe clinical and genetic findings of an early onset SCCMS patient carrying a very rare missense mutation c.880C > T in CHRND causing a highly conserved leucine to phenylalanine substitution in the M2 domain of CHRND. The patient had no repetitive CMAP. He had a dramatic response to fluoxetine at low–moderate doses (40 mg/day), increasing over months: Being wheelchair bound, he could walk independently after treatment. Rare cases may offer insight into the pathological gating mechanism leading to CMS. SCCMS should be suspected even without a repetitive CMAP. Fluoxetine at relatively low doses can be a very effective treatment.
CRIS-Team Scopus Importer:2020-10-16
Keywords: AChR delta subunit; CHRND; Congenital myasthenic syndromes; Fluoxetine; Slow channel

Reduced muscle strength in ether lipid-deficient mice is accompanied by altered development and function of the neuromuscular junction - Dorninger, Fabian; Herbst, Ruth; Kravic, Bojana; Camurdanoglu, Bahar Z.; Macinkovic, Igor; Zeitler, Gerhard; Forss-Petter, Sonja; Strack, Siegfried; Khan, Muzamil Majid; Waterham, Hans R.; Rudolf, Ruediger; Hashemolhosseini, Said; et al. (Journal of Neurochemistry, 2017)
Inherited deficiency in ether lipids, a subgroup of phospholipids whose biosynthesis needs peroxisomes, causes the fatal human disorder rhizomelic chondrodysplasia punctata. The exact roles of ether lipids in the mammalian organism and, therefore, the molecular mechanisms underlying the disease are still largely enigmatic. Here, we used glyceronephosphate O-acyltransferase knockout (Gnpat KO) mice to study the consequences of complete inactivation of ether lipid biosynthesis and documented substantial deficits in motor performance and muscle strength of these mice. We hypothesized that, probably in addition to previously described cerebellar abnormalities and myelination defects in the peripheral nervous system, an impairment of neuromuscular transmission contributes to the compromised motor abilities. Structurally, a morphologic examination of the neuromuscular junction (NMJ) in diaphragm muscle at different developmental stages revealed aberrant axonal branching and a strongly increased area of nerve innervation in Gnpat KO mice. Post-synaptically, acetylcholine receptor (AChR) clusters colocalized with nerve terminals within a widened endplate zone. In addition, we detected atypical AChR clustering, as indicated by decreased size and number of clusters following stimulation with agrin, in vitro. The turnover of AChRs was unaffected in ether lipid-deficient mice. Electrophysiological evaluation of the adult diaphragm indicated that although evoked potentials were unaltered in Gnpat KO mice, ether lipid deficiency leads to fewer spontaneous synaptic vesicle fusion events but, conversely, an increased post-synaptic response to spontaneous vesicle exocytosis. We conclude from our findings that ether lipids are essential for proper development and function of the NMJ and may, therefore, contribute to motor performance. Read the Editorial Highlight for this article on page 463.
EVALuna2:33477

Restricted expression of mGCMa in kidney ind thymus - Hashemolhosseini, Said; Hadjihannas, Michel; Haase, Christian; Amann, Kerstin Ute; Wegner, Michael (Mechanisms of Development, 2002)
UnivIS-Import:2015-04-14:Pub.2002.forsch.sonder.sfb423.restri

Restricted expression of mouse GCMa/Gcm1 in kidney and thymus - Hashemolhosseini, Said; Stolt, Claus; Wegner, Michael; et al. (Mechanisms of Development, 2002)
Mouse Glial Cells Missing a (mGCMa) belongs to a small family of transcription factors named after the prototypical GCM from Drosophila. mGCMa was expected to regulate gliogenesis, but instead found to be primarily expressed during development in trophoblasts of chorion and labyrinth. Its deletion causes abnormal placental labyrinth formation and results in embryonic lethality. Here we identify kidney and thymus as sites of mGCMa expression. In thymus, mGCMa is restricted to few small clusters of cells, in kidney to the S3 segment of proximal tubules. mGCMa expression is primarily postnatal, arguing for a role in organ function rather than organ development. © 2002 Elsevier Science Ireland Ltd. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2002.med.IB.LPCIPDBI.restri
Keywords: GCM; Kidney; Thymus; Proximal tubule; S3 segment

Structure of the GCM domain-DNA complex: a DNA-binding domain with a novel fold and mode of target site recognition - Wegner, Michael; Hashemolhosseini, Said; et al. (EMBO Journal, 2003)
Glia cell missing (GCM) transcription factors form a small family of transcriptional regulators in metazoans. The prototypical Drosophila GCM protein directs the differentiation of neuron precursor cells into glia cells, whereas mammalian GCM proteins are involved in placenta and parathyroid development. GCM proteins share a highly conserved 150 amino acid residue region responsible for DNA binding, known as the GCM domain. Here we present the crystal structure of the GCM domain from murine GCM bound to its octameric DNA target site at 2.85 Å resolution. The GCM domain exhibits a novel fold consisting of two domains tethered together by one of two structural Zn ions. We observe the novel use of a β-sheet in DNA recognition, whereby a five-stranded β-sheet protrudes into the major groove perpendicular to the DNA axis. The structure combined with mutational analysis of the target site and of DNA-contacting residues provides insight into DNA recognition by this new type of Zn-containing DNA-binding domain.
UnivIS-Import:2015-03-09:Pub.2003.med.IB.LPCIPDBI.struct
Keywords: DNA recognition; Glia cells; Transcription factor; X-ray crystal structure; Zn-binding

The desmin mutation R349P increases contractility and fragility of stem cell-generated muscle micro-tissues - Spörrer, Marina; Kah, Delf-Thorge Eric; Gerum, Richard; Reischl, Barbara; Huraskin, Danyil; Dessalles, Claire A.; Schneider, Werner; Goldmann, Wolfgang; Herrmann, Harald; Thievessen, Ingo; Clemen, Christoph S.; Friedrich, Oliver; et al. (Neuropathology and Applied Neurobiology, 2021)
Aims: Desminopathies comprise hereditary myopathies and cardiomyopathies caused by mutations in the intermediate filament protein desmin that lead to severe and often lethal degeneration of striated muscle tissue. Animal and single cell studies hinted that this degeneration process is associated with massive ultrastructural defects correlating with increased susceptibility of the muscle to acute mechanical stress. The underlying mechanism of mechanical susceptibility, and how muscle degeneration develops over time, however, has remained elusive. Methods: Here, we investigated the effect of a desmin mutation on the formation, differentiation, and contractile function of in vitro-engineered three-dimensional micro-tissues grown from muscle stem cells (satellite cells) isolated from heterozygous R349P desmin knock-in mice. Results: Micro-tissues grown from desmin-mutated cells exhibited spontaneous unsynchronised contractions, higher contractile forces in response to electrical stimulation, and faster force recovery compared with tissues grown from wild-type cells. Within 1 week of culture, the majority of R349P desmin-mutated tissues disintegrated, whereas wild-type tissues remained intact over at least three weeks. Moreover, under tetanic stimulation lasting less than 5 s, desmin-mutated tissues partially or completely ruptured, whereas wild-type tissues did not display signs of damage. Conclusions: Our results demonstrate that the progressive degeneration of desmin-mutated micro-tissues is closely linked to extracellular matrix fibre breakage associated with increased contractile forces and unevenly distributed tensile stress. This suggests that the age-related degeneration of skeletal and cardiac muscle in patients suffering from desminopathies may be similarly exacerbated by mechanical damage from high-intensity muscle contractions. We conclude that micro-tissues may provide a valuable tool for studying the organization of myocytes and the pathogenic mechanisms of myopathies.
CRIS-Team Scopus Importer:2021-12-17
Keywords: desmin; desminopathy; micro-tissue; skeletal muscle physiology; tissue engineering

The impact of autophagy on peripheral synapses in health and disease - Rudolf, Rudiger; Khan, Muzamil Majid; Wild, Franziska; Hashemolhosseini, Said (Frontiers in Bioscience, 2016)
Alterations of autophagy have been linked to several peripheral nervous system diseases, such as amyotrophic lateral sclerosis and Charcot-Marie-Tooth disease. Modulation of autophagy by metabolic or pharmacological interventions has been increasingly recognized as a strategy to fight many of these disorders. Cellular processes that are aberrant in case of impaired autophagy and that might lead to these diseases belong to three different categories: (1) clearing of protein aggregates, (2) regulation of vesicle and cargo turnover, and (3) disposal of damaged mitochondria. This review summarizes the present literature that addresses both, the impact and mechanisms of autophagy on the health of the peripheral nervous system and treatment proposals for human disorders associated with impaired autophagy.
EVALuna2:4992

The role of protein kinase CK2 in skeletal muscle: Myogenesis, neuromuscular junctions, and rhabdomyosarcoma - Hashemolhosseini, Said (Neuroscience Letters, 2020)
For the first time, a review article focuses exclusively on the role of the protein kinase CK2 in mono- and poly-nucleated mammalian skeletal muscle cells. While CK2, a pleiotropic serine/threonine kinase was originally thought to phosphorylate mainly casein, later evidence found glycogen phosphorylase and glycogen synthase also to be a target, linking the enzyme to muscle biology. Indeed, recent studies have shown that CK2 is involved in many different steps in the biology of striated skeletal muscle, such as myogenesis and homeostasis in the adult muscle, and even at the neuromuscular junctions, the points of contact between the muscle fibers and the motor nerves end. Next to the role of CK2 in muscle physiology, this review also highlights the contribution of CK2 in muscle pathologies, such as muscle tumors and myopathies.
CRIS-Team Scopus Importer:2020-05-15
Keywords: Myogenesis; Neuromuscular junction; Protein kinase CK2; Rhabdomyosarcoma; Skeletal muscle

Wnt/?-catenin signaling via Axin2 is required for myogenesis and, together with YAP/Taz and Tead1, active in IIa/IIx muscle fibers - Huraskin, Danyil; Eiber, Nane; Reichel, Martin; Zidek, Laura M.; Kravic, Bojana; Bernkopf, Dominic; von Maltzahn, Julia; Behrens, Jürgen; Hashemolhosseini, Said (Development, 2016)
Canonical Wnt/?-catenin signaling plays an important role in myogenic differentiation, but its physiological role in muscle fibers remains elusive. Here, we studied activation of Wnt/?-catenin signaling in adult muscle fibers and muscle stem cells in an Axin2 reporter mouse. Axin2 is a negative regulator and a target of Wnt/?-catenin signaling. In adult muscle fibers, Wnt/?-catenin signaling is only detectable in a subset of fast fibers that have a significantly smaller diameter than other fast fibers. In the same fibers, immunofluorescence staining for YAP/Taz and Tead1 was detected. Wnt/?-catenin signaling was absent in quiescent and activated satellite cells. Upon injury, Wnt/?-catenin signaling was detected in muscle fibers with centrally located nuclei. During differentiation of myoblasts expression of Axin2, but not of Axin1, increased together with Tead1 target gene expression. Furthermore, absence of Axin1 and Axin2 interfered with myoblast proliferation and myotube formation, respectively. Treatment with the canonical Wnt3a ligand also inhibited myotube formation. Wnt3a activated TOPflash and Tead1 reporter activity, whereas neither reporter was activated in the presence of Dkk1, an inhibitor of canonical Wnt signaling. We propose that Axin2-dependent Wnt/?-catenin signaling is involved in myotube formation and, together with YAP/Taz/Tead1, associated with reduced muscle fiber diameter of a subset of fast fibers.
EVALuna2:4993